Coins of War and Triumph of Octavian. The CAESAR DIVI F and IMP CAESAR Series (RIC I2 250-274) - Néstor F. Marqués González (Sagvntum, 2015)
In 2014 we celebrated the bimillennial anniversary of the death of Augustus, one of the most prominent figures of the ancient world. His policy and morals marked a major shift for the Roman State, thanks partly to his masterful use of political propaganda. Octavian, after becoming his great-uncle’s heir, made good use of public manipulation to achieve his goals during the triumvirate and the subsequent conflicts. Now we are presenting a collection of his political and military propaganda in this last period of the Republic in which Rome went from the triumvirate to the civil war and the subsequent proclamation of the young Octavian as Augustus. We deal with war coins minted between the battles of Naulochus and Actium and the representations of the subsequent triumphs that resulted in the final ascent of a young man with pretensions of power who got to rule the world.